Auto Hand Washing Implementation Based Microcontroller Using Independent Power Source: Implementasi Pencuci Tangan Otomatis Berbasis Mikrokontroler dengan Sumber Energi Mandiri - Tino Suhaebri; Asma Ainuddin (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2023)
The world is facing the beginning of the covid 19 pandemic. Corona Virus Disease (Covid 19) is a disease caused by a new type of virus called SARS-CoV-2. The government's concern about the increasing impact of the virus requires preventive action to be taken by implementing various health protocols, one of which is washing hands. Washing hands with conventional equipment still allows contamination of viruses and bacteria while touching of a water valve or soap pump lever. For this reason, a hand washing system is designed to automatically function without any touch. The control system uses ATMega328 microcontroller, distance sensor, motor driver and DC water pump. The system also designed for areas where electricity is not fully covered, with built in a solar power plant. The results of manufacture and testing show that the system works as well. With a water storage capacity of 19 liters, the hand washing process can be carried out 14 times. Measurements of the PLTS system show that the system can operate for approximately 3 hours with a battery charging time of 3.5 hours.